2016
DOI: 10.1155/2016/7065454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Acceptability of the Internal Gap of CAD/CAM PD-AG Crowns Using Intraoral Digital Impressions

Abstract: The purpose of this study was to compare the internal gap between CAD/CAM palladium-silver crowns and cast gold crowns generated from intraoral digital versus conventional impressions and to determine the clinical acceptability. Nickel-chrome master dies were made from the prepared resin tooth with the conventional impression method (n = 40). For ICC (Intraoral, CAD/CAM) group, 10 intraoral digital impressions were made, and 10 CAD/CAM crowns of a PD-AG (palladium-silver) machinable alloy were generated. For I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Furthermore, in an in vitro study performed by Svanborg et al [40], there was no statistically significant difference in marginal and internal fit values of cobalt-chromium alloy CAD/CAM crowns fabricated fully digitally or after scanning of a conventional cast. In contrast, Kim et al [9] reported that gold casted and palladium-silver alloy milled crowns fabricated after conventional impression making presented a significantly superior internal fit than crowns manufactured fully digitally or after digital impression and printing of the working cast. However, a clinical trial from Koulivand et al [42] resulted in a significantly lower marginal discrepancy for the digital group (TRIOS scanner) than conventionally manufactured cobalt-chromium alloy milled crowns.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, in an in vitro study performed by Svanborg et al [40], there was no statistically significant difference in marginal and internal fit values of cobalt-chromium alloy CAD/CAM crowns fabricated fully digitally or after scanning of a conventional cast. In contrast, Kim et al [9] reported that gold casted and palladium-silver alloy milled crowns fabricated after conventional impression making presented a significantly superior internal fit than crowns manufactured fully digitally or after digital impression and printing of the working cast. However, a clinical trial from Koulivand et al [42] resulted in a significantly lower marginal discrepancy for the digital group (TRIOS scanner) than conventionally manufactured cobalt-chromium alloy milled crowns.…”
Section: Resultsmentioning
confidence: 91%
“…Specifically, zirconia-, lithium disilicate-, and PFM/alloy-based restorations were investigated in terms of marginal discrepancy after digital vs. conventional impression making. In five of the selected articles, the investigators included protocols that tested more than one restorative material, that is, zirconia, lithium disilicate, or alloys [9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…However, digital impressions using IOS have facilitated the designing of zirconia superstructures using CAD and machining using CAM [ 16 , 17 ], which have streamlined the process of prosthesis fabrication; thus, reducing the treatment time, laboratory time, and errors [ 8 , 18 ]. Several studies have reported on the performance of IOSs.…”
Section: Discussionmentioning
confidence: 99%
“…Kolejnym krokiem jest planowanie, projektowanie i realizacja leczenia protetycznego przez wykonanie uzupełnień protetycznych. 2,3 Innym zastosowaniem odwrotnej inżynierii może być kontrola wykonanych uzupełnień protetycznych przed ich zacementowaniem w jamie ustnej pacjenta. 4 Dzięki możliwości dokładnego skanowania zarówno modeli pacjenta, jak i powierzchni uzupełnienia protetycznego przy użyciu skanerów laboratoryjnych o wysokiej rozdzielczości, możliwe jest skontrolowanie parametrów dopasowania i szczelności brzeżnej uzupełnienia protetycznego bez…”
Section: Wstępunclassified
“…Wielu autorów podkreśla ich istotność z punktu widzenia prewencji powstawania próchnicy wtórnej pod uzupełnieniem, czy zapobieganiu odcementowaniu, a co za tym idzie, długoczasowej przeżywalności tego typu prac. 3,5 Z tego powodu, uznano właśnie te parametry, jako najważniejsze na początkowym etapie weryfikacji metodą inżynierii odwrotnej. W celu wykonania uzupełnień protetycznych, możliwe jest wykorzystanie wielu materiałów.…”
Section: Introductionunclassified